A Comparative Study on the Viability of Normal and Cancerous Cells upon Irradiation with a Steady Beam of THz Rays - Larysa Kovalevska; Olexandr Golenkov; Yelyzaveta Kulahina; Todd Callender; Fedir Sizov; Elena Kashuba (Life, 2022)
Terahertz (THz) electromagnetic radiation is commonly used in astronomy, security screening, imaging, and biomedicine, among other applications. Such approach has raised the question of the influence of THz irradiation on biological objects, especially the human body. However, the results obtained to date are quite controversial. Therefore, we performed a comparative study on the viability of normal cells and cancer cells upon irradiation with a steady beam of THz rays. We used human peripheral blood mononuclear cells and cancer cell lines. Primary human mononuclear blood cells (monocytes, and B-, and T-cells) showed an increased death rate, determined by cell counting and fluorescence microscopy, upon 0.14 THz irradiation. The effect of THz radiation was different among malignant cells of B- and T-cell origin (Ramos and Jurkat cells) and epithelial cancer cells (MCF7 and LNCaP). This was demonstrated by cell counting and by the alamarBlue assay. In conclusion, THz radiation can result in the death of human primary and malignant cells. However, the mechanism of this phenomenon is largely unknown. Hence, more work should be done to shed some light on the mechanism of action of THz irradiation in living organisms to enhance technologic developments.